Comparative characterization of the performance of bio-aerosol nebulizers in connection with atmospheric simulation chambers - S. G. Danelli; S. G. Danelli; M. Brunoldi; M. Brunoldi; D. Massabò; D. Massabò; F. Parodi; V. Vernocchi; V. Vernocchi; P. Prati; P. Prati (Atmospheric Measurement Techniques, 2021)
The interplay of bio-aerosol dispersion and impact, meteorology, and air quality is gaining increasing interest in the wide spectrum of atmospheric sciences. Experiments conducted inside confined artificial environments, such as atmospheric simulation chambers (ASCs), where atmospheric conditions and composition are controlled, can provide valuable information on bio-aerosol viability, dispersion, and impact. We focus here on the reproducible aerosolization and injection of viable microorganisms into an ASC, the first and crucial step of any experimental protocol to expose bio-aerosols to different atmospheric conditions. We compare the performance of three nebulizers specifically designed for bio-aerosol applications: the Collison nebulizer, the Blaustein Atomizing Modules (BLAM), and the Sparging Liquid Aerosol Generator (SLAG), all manufactured and commercialized by CH TECHNOLOGIES. The comparison refers to operating conditions and the concentration of viable bacteria at the nebulizer outlet, with the final goal being to measure the reproducibility of the nebulization procedures and assess their application in experiments inside ASCs. A typical bacterial test model, Escherichia coli (ATCC® 25922™), was selected for such characterization. Bacteria suspensions with a concentration around 108 CFU mL−1 were first aerosolized at different air pressures and collected by a liquid impinger to obtain a correlation curve between airflow and nebulized bacteria for each generator. Afterwards, bacteria were aerosolized inside the atmospheric simulation chamber ChAMBRe (Chamber for Aerosol Modelling and Bio-aerosol Research) to measure the reproducibility of the whole procedure. An overall reproducibility of 11 % (i.e., standard deviation of the results obtained with the three nebulizers) was obtained with each nebulizer through a set of baseline experiments.